Effects of different exercise interventions on lower back pain: a systematic review and meta-analysis - Liu, Xingchi; Gao, Wenbo; Wu, Peirun; Huang, Jiawang; Han, Jingjing; Xu, Xiuli; Chen, Wanqiang (Frontiers in Physiology, 2026)
ObjectiveLower back pain (LBP) is the leading cause of disability worldwide. This study evaluates the pain relief and functional benefits of exercise interventions for affected individuals to inform clinical practice.MethodsWe searched nine electronic databases for randomized controlled trials (RCTs) that examined exercise interventions for LBP.ResultsWe included 35 RCTs (n = 2,132). Exercise interventions were categorized into eight types: Pilates, yoga, core training, tai chi, walking, stretching, cycling, and deep-water running. Compared to usual care or other types of pain management interventions, exercise interventions demonstrated a significant overall difference in reducing pain (SMD = −0.81, 95% CI −0.91, −0.72; 17.31, P < 0.001). Subgroup analysis revealed that tai chi (SMD = −0.95), walking (MD = −1.05), and Pilates (MD = −1.14) exhibited the most significant analgesic effects. Regarding functional disability improvement, assessment using the Oswestry Disability Index showed significant efficacy for walking (MD = −6.34, P < 0.001), Pilates (MD = −4.73, P < 0.0001), and yoga (MD = −3.41, P = 0.002). However, assessment using the Roland–Morris Disability Questionnaire (RMDQ) indicated that only Pilates resulted in significant improvement (MD = −2.34, P < 0.001).ConclusionPilates, yoga, and walking reduce pain and improve function in non-specific LBP. Tai chi and core-stability training also achieve significant analgesia. The evidence for stretching and cycling remains inconclusive.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251047326, identifier CRD420251047326.